AJUBA: A regulator of epidermal homeostasis and cancer. Issue 4 (26th January 2021) - Schleicher, Krista; Schramek, Daniel
Abstract: The epidermis, outermost layer of the skin, is constantly renewing itself through proliferative and differentiation processes. These processes are vital to maintain proper epidermal integrity during skin development and homeostasis and for preventing skin diseases and cancers. The biological mechanisms that permit this balancing act are vast, where individual pathway regulators are known, but the exact regulatory control and cross‐talk between simultaneously turning one biological pathway on and an opposing one off remain elusive. This review explores the diverse roles the scaffolding protein AJUBA plays during epidermal homeostasis and cancer. Initially identified for its role in promoting meiotic progression in oocytes through Grb2 and MAP kinase activity, AJUBA also maintains cytoskeletal tension permitting epidermal tissue development and responds to retinoic acid committing cells to initiate development of surface epidermal layer. AJUBA regulates proliferation of skin stem cells through Hippo and Wnt signalling and encourages mitotic commitment through Aurora‐A, Aurora‐B and CDK1. In addition, AJUBA also induces epidermal differentiation to maintain appropriate epidermal thickness and barrier function by activating Notch signalling and stabilizing catenins and actin during cellular remodelling. AJUBA also plays an imperative context‐dependent tumor‐promoting and tumor‐suppressive role within epithelial cancers. AJUBA's abundant roles within the epidermis signify its importance as a molecular switchboard, vetting multiple signalling pathways to control epidermal biology.